Digital messaging to improve college enrollment and success. (October 2021) - Avery, Christopher; Castleman, Benjamin L.; Hurwitz, Michael; Long, Bridget Terry; Page, Lindsay C.
Abstract: We investigate the efficacy of text messaging campaigns to support students with key steps in the college search, application, selection and transition process with concurrent cluster randomized control trials. Collaborating with national non-profit organizations, we implemented text-message based outreach to students in the high school graduating class of 2016 in over 700 high schools that primarily serve low-income students. Collaborating with several Texas school districts, we implemented a school-based version of the intervention. In contrast to the national version which produced null and negative effects, the school-based intervention yielded positive and significant impacts on several college-going steps but still only yielded significant impacts on college enrollment and second-year persistence for certain subgroups.